Peran Guru dalam Menghadapi Tantangan Pembelajaran Abad 21 - Siti Syarah S. Tintis; Bakri Hasanuddin; Mohammad Ega Nugraha; Harnida Wahyuni Adda (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article discusses the crucial role of teachers in facing the challenges of 21st century learning at the Inpres Silae State Elementary School (SDN). Education in this era requires adaptation and innovation to suit technological developments and the demands of the times. Teachers at SDN Inpres Silae are expected not only to deliver material, but also as learning facilitators who are able to develop 21st century skills in students. The research method used in this research is a qualitative descriptive method. The data source was obtained from teachers at SDN Inpres Silae. This research examines the role of teachers in facing the learning challenges of the 21st century. Indonesian teachers must be able to overcome the challenges of learning in the 21st century. Teachers must be able to adapt to changing times. If teachers are unable to adapt to this increasingly advanced era, the role of teachers will increasingly change and be replaced by the role of technology and social media as a means of learning. This article can conclude that the role of teachers at SDN Inpres Silae is not only limited to imparting academic knowledge, but includes character building, developing creativity, and preparing students to face the realities of a dynamic world. With this holistic approach, teachers in these schools act as agents of change and move education in a direction that meets the demands of the times.